Grundlegende Untersuchungen zur Herstellung hochfester Aluminiumblechbauteile in einem kombinierten Umform- und Abschreckprozess - Degner, Julia (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
Mobility is the prerequisite for the economic and social development of our modern service and industrial society.To guarantee mobility also in the future, sustainable measures and strategies are needed to increase the effi-ciency of vehicles while at the same time reducing environmental pollution, such as CO2 emissions. One of these strategies is the weight reduction of vehicles based on light-weight strategies and materials. Due to the high strength and low density, the focus of research has recently been on high-strength aluminum alloys, as these can lead to further sheet thickness reductions compared to conventional aluminum alloys and realize light-weight constructions even in safety- and crash-relevant areas. However, the challenge is the limited formability of these alloys, which is why tempera-ture-assisted forming processes are usually used. A new approach is the combined forming and quenching process. By means of a heat treatment in combination with an immediate forming and simultaneous quenching, the production of sophisticated component geometries can be enabled, which in turn can be optimized to the highest strengths by means of ageing pro-cesses. The aim of this work was to generate a basic process understanding for the manufacturing of high-strength aluminum sheet metal components within the framework of a combined forming and quenching process. The focus was on the definition of boundary conditions during heat treatment on the basis of a sensitivity analysis, the process design based on a thermal and mechanical material characterization as well as the process analysis and evaluation to identify the potential of a combined forming and quench-ing process using a demonstrator componen